2007
DOI: 10.1016/s0929-6646(08)60084-4
|View full text |Cite
|
Sign up to set email alerts
|

Antivenom Therapy for Crotaline Snakebites: Has the Poison Control Center Provided Effective Guidelines?

Abstract: Crotaline snakebites (Protobothrops mucrosquamatus and Trimeresurus stejnegeri) are a common medical emergency in Taiwan that can be effectively treated by a bivalent F(ab)2 antivenom. We investigated the differences in the clinical outcomes of patients who received different therapeutic regimens of antivenom in a medical center where clinical toxicologists followed the poison control center (PCC) guidelines (medical group) and surgeons did not (surgical group). The medical records of inpatients with crotaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
0
17
2
Order By: Relevance
“…Although some authors suggested that treatment with FH antivenom is administration of 1 vial every 2 hours until clinical stabilization and a maximum administration of 4 vials in the FH group snakebites patients. 6 As for tissue necrosis, compartment syndrome due to limb swelling, the TPCC guideline clearly stated surgical treatment is not allowed unless deep tissue necrosis or compartment syndrome developed. Lacking these important recommendations may make doctors who treat snakebite patients on their free evaluation of severity but not on the basis of evidence medicine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some authors suggested that treatment with FH antivenom is administration of 1 vial every 2 hours until clinical stabilization and a maximum administration of 4 vials in the FH group snakebites patients. 6 As for tissue necrosis, compartment syndrome due to limb swelling, the TPCC guideline clearly stated surgical treatment is not allowed unless deep tissue necrosis or compartment syndrome developed. Lacking these important recommendations may make doctors who treat snakebite patients on their free evaluation of severity but not on the basis of evidence medicine.…”
Section: Discussionmentioning
confidence: 99%
“…13e16 One singlecenter study found that although patients who were treated by surgeons had been administered a higher FH antivenom dosage (5.9 AE 4.2 vials) than those who were treated by emergency medicine physicians (2.7 AE 1.6 vials), in accordance with the TPCC guideline both groups of patients experienced similar outcomes. 6 Thus, the TPCC guidelines for treatment with FH antivenom may need little revision by adding severity grading systems to guide the antivenom dosage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are six main kinds of venomous snakes in Taiwan, including Naja atra (cobra), Bungarus multicinctus, Trimeresurus mucrosquamatus, Trimeresurus stejnegeri, Deinagkistrodon acutus, and Daboia russelii siamensis (1). Antivenom administration is the standard therapy for snakebite.…”
Section: Introductionmentioning
confidence: 99%
“…54 In Taiwan, only 0.7-3% of patients receiving bivalent T. stejnegeri and P. mucrosquamatus antivenom were reported to have a skin allergy. 55,56 Moreover, anaphylaxis was only reported in this study despite the fact that nearly 1,000 cases received antivenom in Taiwan each year. 1 Because of the overall low incidence of allergic reactions after antivenom administration, routine premedication with epinephrine or antihistamines and corticosteroids is not recommended in Taiwan.…”
Section: Discussionmentioning
confidence: 73%